An examination of an adapter method for measuring the vibration transmitted to the human arms. (September 2015) - Xu, Xueyan S.; Dong, Ren G.; Welcome, Daniel E.; Warren, Christopher; McDowell, Thomas W.
Highlights: An adapter method for measuring vibration on human arms was evaluated. The effects of adapter mass & attachment tightness on measurement were examined. The results measured with lightweight adapters and laser devices were comparable. The transmissibility data may not be comparable before coordinate transformations. Consistent with theory, the transmissibility is correlated with apparent mass. Abstract: The objective of this study is to evaluate an adapter method for measuring the vibration on the human arms. Four instrumented adapters with different weights were used to measure the vibration transmitted to the wrist, forearm, and upper arm of each subject. Each adapter was attached at each location on the subjects using an elastic cloth wrap. Two laser vibrometers were also used to measure the transmitted vibration at each location to evaluate the validity of the adapter method. The apparent mass at the palm of the hand along the forearm direction was also measured to enhance the evaluation. This study found that the adapter and laser-measured transmissibility spectra were comparable with some systematic differences. While increasing the adapter mass reduced the resonant frequency at the measurement location, increasing the tightness of the adapter attachment increased the resonant frequency. However, the use of lightweight (⩽15 g) adapters under medium attachment tightness did not change the basic trends of the transmissibility spectrum. The resonant features observed in the transmissibility spectra were also correlated with those observed in the apparent mass spectra. Because the local coordinate systems of the adapters may be significantly misaligned relative to the global coordinates of the vibration test systems, large errors were observed for the adapter-measured transmissibility in some individual orthogonal directions. This study, however, also demonstrated that the misalignment issue can be resolved by either using the total vibration transmissibility or by measuring the misalignment angles to correct the errors. Therefore, the adapter method is acceptable for understanding the basic characteristics of the vibration transmission in the human arms, and the adapter-measured data are acceptable for approximately modeling the system.